Success Factors of Human Resource Information System Implementation: A Case of Ministry of State-owned Enterprise - Wita Puspitarini; Putu Wuri Handayani; Ave Adriana Pinem; Fatimah Azzahro (Proceeding of the Electrical Engineering Computer Science and Informatics, 2018)
This study aims to analyze factors influencing the successful implementation of Human Resources Information System (HRIS) at the Ministry of State-Owned Enterprises (MSOE). There are 22 factors influence the success of HRIS implementation that are categorized into 4 dimensions, namely human, organization, technology and environment based on DeLone & McLean information system success model, HOT (human-organization-technology) fit model and TOE (technology-organization-environment). This research use quantitative method approach and data collection is gathered using questionnaire. Method of data analysis using Entropy method to calculate the weight of success factors and dimensions, and rank factors and dimensions. There are 99 respondents of the HRIS users provided data through the questionnaires distributed to them. This study shows that the dimensions influencing the success of HRIS implementation at the MSOE in priority order are technology, human, environment and organization. In addition, there are 5 factors selected with the highest weights namely information quality, service quality, top management support, system quality and social influence.